Los comerciantes franceses en la Málaga del siglo XVIII - Villar García, María Begoña (Universidad de Málaga. Facultad de Filosofía y Letras, 2009)
Este artículo estudia la evolución de los comerciantes franceses instalados en Málaga a lo largo del siglo XVIII. La dinastía borbónica los favoreció pero no lograron su autentica consolidación hasta el último tercio del siglo. De mercaderes de vara pasaron a ser miembros del “Comercio Marítimo” e impulsores de las iniciativas económicas que se crearon en la ciudad en ese periodo. También sufrieron las consecuencias negativas de la Revolución y de la invasión napoleónica en España.

This article deals with French traders settled in Malaga in the course of XVIII century. They were helped by the Bourbon dynasty but they didn’t obtain a real consolidation until the last third of the century. At the beginning, they were stick traders but finally became members of the ‘Comercio Marítimo’ (Seatrade) and they encouraged economic initiatives in Malaga during this period. However, they also suffered negative consequences of the Revolution and the Napoleonic invasion of Spain.
Keywords: Málaga - Comercio - Francia - S. XVIII; Crisis; Compañías privilegiadas; Mercaderes de vara; Comercio; Franceses; Crisis; Privileged company; Stick traders; Trade; French